Analysis of the Impact of Land Tenure Certificates with Both the Names of Wife and Husband in Vietnam - World Bank (Washington, DC, 2012)
The 2003 land law defines that the Land Tenure Certificate (LTCs) carries both the wife's and husband's names. Theoretically, the requirement of both the wife's and husband's names on the LTCs aims at enabling the wife to participate more actively in household economic production for poverty reduction, and to protect the rights of the woman in the event of civil disputes over the land that has been provided with a LTCs. A field-based research was conducted in order to assess whether the joint-title LTCs has had positive impacts on the household in general and on the woman's roles in the household in particular, as intended by the 2003 land law. The report is organized in three sections: (1) introduction; (2) study findings with five contents: access to credit; investment opportunities and outcomes; land use rights security; impacts on women's position in family and in community; and issuance and conversion of LTCs; and (3) proposals to land administration agencies.